The PENGARUH GAYA HIDUP , KERAGAMAN PRODUK, DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA POLYGON PADA TOKO SEPEDA REJO BARAT MAGETAN - Zindy Puspitaningrum (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
At this time two-wheeled bicycles or commonly called ontel bicycles are still favored by many Indonesian people. Not only as a means of transportation, bicycles have now become a lifestyle for Indonesian people. These two-wheeled bicycles became a trend again around the 2005s, reducing congestion, maintaining physical health ,facilities supported by government institutions, several factors contributing to this include the increase in gasoline prices, environmental awareness to create clean air in urban areas and concern for threats. global warming, or just following a lifestyl. In this think about, utilizing quantitative strategies with overview investigate that employments a survey as an instrument. For preparing the survey information that has been dispersed utilizing the SPSS 24 application. The population in this study are consumers who have bought Polygon bicycle products and are domiciled in Ngawi Regency. The samples taken were the riding community in Ngawi district and the polygon bicycle user community in Ngawi district. The test information employments the Non Likelihood Testing strategy (arbitrary inspecting) with the Purposive Examining method, totaling 100 respondents. The information investigation strategy utilized is numerous straight relapse investigation. The comes about of this consider show that the free factors, specifically Way of life, Item Differences, and Item Costs, influence the subordinate variable, specifically Buy Choices by individuals who purchase Polygon bikes at the Rejo Barat bike shop, Magetan.